Abnormal Fractional Amplitude of Low Frequency Fluctuation Changes in Patients With Dry Eye Disease: A Functional Magnetic Resonance Imaging Study - Liang, Rong-Bin; Liu, Li-Qi; Shi, Wen-Qing; Sun, Tie; Ge, Qian-Min; Li, Qiu-Yu; Shu, Hui-Ye; Zhang, Li-Juan; Shao, Yi (Frontiers in Human Neuroscience, 2022)
Purpose:To investigate spontaneous brain activity in patients with dry eye (DE) and healthy control (HC) using the fractional amplitude of low frequency fluctuation (fALFF) technique with the aim of elucidating the relationship between the clinical symptoms of DE and changes in brain function. Material and Methods: A total of 28 patients with DE and 28 matched healthy volunteers (10 males and 18 females in each group) were enrolled. Resting-state functional magnetic resonance imaging scans were performed in both groups.Then all subjects were required to complete a comprehensive Hospital Anxiety and Depression Scale (HADS).Receiver operating characteristic (ROC) curve analysis was used to evaluate the differences in fALFF values between the two groups and their diagnostic value. Linear correlations between HADS and fALFF values in different brain regions of DE patients were analyzed using Pearson correlation coefficient. Results: Patients with DE had significantly higher fALFF values in the left calcarine sulcus(CS)than the HC group, while fALFF values in the bilateral middle frontal gyrus(MFG)and right MFG/right inferior frontal gyrus(IFG) were significantly lower in DE patients than in HC group. fALFF values had a high diagnostic value for differentiating patients with DE from HC group (P < 0.001). Right MFG and right MFG/IFG were significantly correlated with HADS values. Conclusion: Our study found that DE mainly involved functional disorders in the brain areas of the left CS, bilateral MFG and right MFG/right IFG , which helped us to find possible clinical features of DE disease and reflected the potential pathological mechanism of DE .